2022
DOI: 10.3389/fendo.2022.1001563
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid metabolism-related genes in bronchoalveolar lavage fluid unveil prognostic and immune infiltration in idiopathic pulmonary fibrosis

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a chronic and progressive condition with an unfavorable prognosis. A recent study has demonstrated that IPF patients exhibit characteristic alterations in the fatty acid metabolism in their lungs, suggesting an association with IPF pathogenesis. Therefore, in this study, we have explored whether the gene signature associated with fatty acid metabolism could be used as a reliable biological marker for predicting the survival of IPF patients.MethodsData on the fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…In our study, the patients with IPF had significantly higher circulating levels of several lipid species, including multiple long-chain acylcarnitines and ceramides and one sphingomyelin species, compared with the controls. These findings are consistent with data showing dysregulated fatty acid or lipid metabolism in mouse models of IPF [ 16 , 32 ], elevated free fatty acids or dysregulation of fatty acid metabolism-related genes in the lungs of patients with IPF [ 16 , 33 ], and elevated circulating levels of fatty acids in patients with IPF [ 19 , 21 , 34 ]. The pattern of higher levels of NEFA along with higher levels of acylcarnitines and select ceramides in patients with IPF in our study points to enhanced availability of fatty acids, possibly due to lipolysis related to wasting.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, the patients with IPF had significantly higher circulating levels of several lipid species, including multiple long-chain acylcarnitines and ceramides and one sphingomyelin species, compared with the controls. These findings are consistent with data showing dysregulated fatty acid or lipid metabolism in mouse models of IPF [ 16 , 32 ], elevated free fatty acids or dysregulation of fatty acid metabolism-related genes in the lungs of patients with IPF [ 16 , 33 ], and elevated circulating levels of fatty acids in patients with IPF [ 19 , 21 , 34 ]. The pattern of higher levels of NEFA along with higher levels of acylcarnitines and select ceramides in patients with IPF in our study points to enhanced availability of fatty acids, possibly due to lipolysis related to wasting.…”
Section: Discussionsupporting
confidence: 91%
“…In studies in patients with IPF, negative correlations were observed between levels of select signaling lipids in peripheral blood and lung function [ 34 ], and higher levels of certain triglycerides and phosphatidylcholines were found in the plasma of patients with more rapid progression [ 21 ]. A risk model based on expression of select fatty acid genes in bronchoalveolar lavage fluid predicted outcomes among patients with IPF [ 33 ]. In our study, higher levels of ceramide C18:1/C16:0 was associated with more severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…identi ed ve fatty acid metabolite-related genes (FAMRG) in bronchoalveolar lavage uid of IPF patients (50). Additionally, Miriana d'Alessandro found differential lipid metabolites in IPF alveolar lavage uid, however, these lipid metabolites do not possess diagnostic value in serum for distinguishing IPF from hypersensitivity pneumonitis (fHP) (51).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that lung fibrosis is sensitively affected by lipid changes [ 46 ]. Impairments and changes in fatty acid metabolism are associated with the pathogenesis of pulmonary fibrosis, and changes in the profile and metabolome of fatty acids are associated with disease progression and outcome [ 47 ]. The accumulation of triglyceride in the form of lipid droplets in alveolar epithelial cells induces endoplasmic reticulum (ER) stress and induces apoptosis of these cells through the expression of TGF-β1 [ 48 ].…”
Section: Discussionmentioning
confidence: 99%